RARE AND ENDANGERING SPECIES OF HERBAL PLANTS GROWING IN THE FOREST PARK OF PEOPLE FRIENDSHIP (DNIPRO CITY) (Ecological Bulletin of Kryvyi Rih District, 2025)
For the Red Book plants of the Dnipropetrovsk region, more and more attention should be paid every year to the protection of the habitats of species growing in urban areas - in urban communities. . Their status and ecological value are of direct importance for strengthening phytocenotic relationships between plants in the environment.. Plants of natural phytocenoses that have survived in the park zone of the city of Dnipro have adapted to such harsh conditions due to changes that are reflected in the functioning of plant organisms. Due to this, only species that have acquired adaptive abilities to environmental conditions can grow. Thus, in the Druzhby narodiv forest park, areas of natural phytocenoses have been preserved in their original state, which include rare plant species belonging to steppe, meadow and swamp vegetation. In accordance with the law of Ukraine "Red Book of Ukraine" of February 7, 2002, we have included a list of plant species that are under threat of extinction in this category of plants. Based on the research conducted in this park, an inventory list of rare herbaceous plants was compiled.
Keywords: industrial city, park area, Red Book plants, rare and endangered species.